Faktor Risiko Kejadian Unmet Need KB di Desa Keseneng Kecamatan Sumowono Kabupaten Semarang - Sohibun Sohibun (Fakultas Kesehatan Masyarakat Universitas Diponegoro, 2015)
Background: The largest percentage of unmet need for family planning in Keseneng village Sumowono sub-district Semarang Regency is 31.7%. Objectives: The objectives of this study is analyze the factors associated with unmet need for family planning in Keseneng Villlage Sumowono Sub-district Semarang Regency. Methods: This study is an explanatory research with a case control study design. The population is marriage female 15-49 years, amounting to 287 people. The sample size of case group and control groups respectively 29 married women. The simple random sampling method was adopted. Analysis of the data descriptively and analytically using the Chi Square ( X2 ) at significance level α= 5%. Results: the percentage of unmet need for family planning due to limiting pregnancy is 100,0%. The variables have difference in the proportion of unmet need for family planning is the husband's support of contraception (p= 0.044 ; OR= 6.1; 95 % CI= 1.2 to 31.2) and women’s Information Education and Communication of contraceptive was received (p= 0.004; OR= 5,9 95%CI 1,9 – 18,7). The variables have not difference in the proportion of unmet need for family planning is the knowledge of contraception (p= 0.297; OR= 2.8; 95 % CI= 0.6 to 11.9 ), discussion of family planning in the family (p= 0.101 ; OR = 2.9 ; 95 % CI = 0.9 to 8.9 ), and the side effects of contraception (p= 0.289 ; OR= 2.0; 95 % CI= 0.7 to 5.8 ). Conclusions : The variables have difference in the proportion of unmet need for family planning is the husband's support of contraception and women’s Information Education and Communication of contraceptive was received. Suggestion: necessary counseling for husband the importance of providing support and wife in terms of discussions about contraception and family planning, and increasing the Communication Information Education on risk if occur pregnancy when not using contraception during still menstruation, also giving information about knowledge of contraception , especially in terms of types of female condoms , side effects of contraceptive ( high blood pressure , hair loss , and sensitive / irritable ) and resources contraception ( mass media , pharmacy , electronic media)